2013
DOI: 10.1186/1756-0500-6-372
|View full text |Cite
|
Sign up to set email alerts
|

Dengue 2 infection of HepG2 liver cells results in endoplasmic reticulum stress and induction of multiple pathways of cell death

Abstract: BackgroundA number of studies have implicated the direct involvement of the liver in dengue virus (DENV) infection, and it has been widely shown that liver cells subsequently undergo apoptosis. The mechanism by which liver cells undergo apoptosis in response to DENV infection remains unclear. To provide further information on the mechanism of apoptosis in DENV infected liver cells, HepG2 cells were infected with DENV 2 and analyzed for the induction of ER stress, apoptosis and autophagy.ResultsIn response to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 92 publications
(146 reference statements)
1
43
0
Order By: Relevance
“…Colocalization between DENV 2 E protein and GRP78 has been previously reported1629, and to confirm this as well as provide evidence on the possible colocalization between DENV 4 E protein and GRP78, HEK293T/17 cells were mock-infected or infected with DENV 2 or DENV 4 and at 1 d.p.i. cells were collected and examined under a confocal microscope after staining with antibodies against DENV E protein and GRP78.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Colocalization between DENV 2 E protein and GRP78 has been previously reported1629, and to confirm this as well as provide evidence on the possible colocalization between DENV 4 E protein and GRP78, HEK293T/17 cells were mock-infected or infected with DENV 2 or DENV 4 and at 1 d.p.i. cells were collected and examined under a confocal microscope after staining with antibodies against DENV E protein and GRP78.…”
Section: Resultssupporting
confidence: 76%
“…Studies have previously shown increased expression of GRP78 during DENV infection162029. To confirm this, as well as to investigate the expression of VDAC during infection, HEK293T/17 cells were mock-infected or infected with DENV 2 or DENV 4 and levels of GRP78 and VDAC determined on days 1–3 p.i by western blotting.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…There are several possible explanations for this discrepancy. However, this simply may reflect that activation of apoptosis is complex and can be triggered through multiple pathways depending on experimental conditions such as MOI and tissue type (Klomporn et al , 2011; McLean et al , 2011; Pattanakitsukul et al , 2007; Theparrit, et al , 2013; Zargar et al , 2011). We note that in Ocampo et al both the range of titers of DENV used for infection and corresponding oral susceptibility seen with their refractory and susceptible strains were higher than those used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in liver cells infected with DENV2, it was observed that PERK and ATF6 were not associated with BiP, resulting in increased eIF-2α phosphorylation (Thepparit et al, 2013). …”
Section: Cellular Stress Pathwaysmentioning
confidence: 99%